THE SOCIOLOGICAL VIEW OF THE NATIONAL ELECTRICITY COMPANY FACED WITH THE PROBLEM OF ELECTRIC CURRENT IN THE CITY OF KISANGANI. - Antoine, MOMELA LISOMA (IJRDO-Journal of Applied Science, 2022)
Indeed, our study focused on the National Electricity Company facing the problem of supplying electric current in the city of Kisangani, case of Tshopo. In this study, our research objective was to talk about the multiple problems related to the operations of supply and consumption of electric current in the commune of Tshopo.